Method for preparing high-tap-density iron phosphate from lithium extraction slag, high-tap-density iron phosphate and application of high-tap-density iron phosphate

By optimizing the preparation process of iron phosphate, including acid dissolution, precipitation, slurry and sintering steps, the tap density of iron phosphate was successfully improved, and the problem of insufficient tap density of iron phosphate in the prior art was solved, which significantly improved the performance of lithium iron phosphate batteries.

CN119637826APending Publication Date: 2025-03-18JIANGXI GANFENG RECYCLING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411975342.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The prior art is difficult to prepare iron phosphate with a tap density higher than 1.0 g/cm3, which limits the performance of lithium iron phosphate batteries.

Method used

By mixing the lithium extract slag with a sulfuric acid solution for acid dissolution, an iron-phosphorus mixed solution was obtained, and then added with ammonia at both ends of the diagonal ends of the reactor, precipitation reaction and rinsing, and then slurry and aged with the sulfuric acid solution, and finally anhydrous iron phosphate was obtained by sintering.

Benefits of technology

The high tap density of iron phosphate (>1.03g/cm3) was achieved, and the performance of lithium iron phosphate batteries was improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637826A_ABST
    Figure CN119637826A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing high-tap-density iron phosphate from lithium extraction slag, the high-tap-density iron phosphate and application of the high-tap-density iron phosphate, and belongs to the technical field of lithium battery material recovery. The method comprises the following steps: mixing the lithium extraction slag and a sulfuric acid solution for acid dissolution to obtain an iron-phosphorus mixed solution; carrying out reaction on the iron-phosphorus mixed solution and ammonia water in a diagonal adding manner, and rinsing to obtain an iron-phosphorus filter cake; and adding a sulfuric acid solution for slurrying and aging to obtain wet iron phosphate dihydrate, and sintering to obtain the anhydrous iron phosphate. The seed crystal reaction of the iron phosphate is optimized into diagonal addition of the iron-phosphorus mixed solution and the ammonia water, so that the particle size distribution of the iron phosphate tends to normal distribution; according to the method, the type and the amount of acid added in the crystallization reaction of the iron phosphate are optimized, primary particles of the iron phosphate are further refined, so that the particles are tightly agglomerated, and the iron phosphate particles with high tap density (the tap density is greater than 1.03 g / cm < 3 >) are successfully prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery material recycling, and in particular to a method for preparing high-tapped iron phosphate from lithium-extracting slag, high-tapped iron phosphate and applications thereof. Background Art

[0002] In recent years, with the increasing demand for energy and the rapid development of the lithium battery industry, the electrical properties of the positive electrode material lithium iron phosphate play a vital role in lithium batteries. As a precursor of lithium iron phosphate, the quality of iron phosphate will greatly determine the performance of lithium iron phosphate batteries. For example, in the process of preparing lithium iron phosphate, the tap density of iron phosphate has a decisive influence on the tap density of lithium iron phosphate. At present, there are many process methods for preparing iron phosphate using waste lithium iron phosphate battery recycling technology, but the tap density of the iron phosphate obtained is mostly lower than 1.0g / cm 3 For example, the tap density of iron phosphate prepared by the prior art is 0.90 g / cm 3 (Patent CN111646447A) and 0.85g / cm 3 (Patent CN110540185A), which is extremely unfavorable for obtaining lithium iron phosphate with high tap density. Therefore, in order to improve the recycling path of waste lithium iron phosphate batteries and improve the performance of recycled lithium iron phosphate, it is very necessary to find a method for preparing high tap density iron phosphate from lithium slag. Summary of the invention

[0003] The object of the present invention is to provide a method for preparing high-tapped iron phosphate from lithium slag, high-tapped iron phosphate and its application, wherein the prepared anhydrous iron phosphate has fine primary particles, tightly agglomerated secondary particles, and extremely high tap density (>1.03 g / cm 3 ).

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing high-compacted iron phosphate from lithium extraction slag, comprising the following steps:

[0006] (1) mixing the lithium extraction slag and sulfuric acid solution, and performing acid dissolution to obtain an iron-phosphorus mixed solution;

[0007] (2) placing the iron-phosphorus mixed solution and ammonia water at two diagonal ends of a reactor, continuously adding the iron-phosphorus mixed solution and ammonia water simultaneously, performing a precipitation reaction, and after solid-liquid separation, performing a first rinsing to obtain a first solid material;

[0008] (3) mixing the first solid material with a sulfuric acid solution to form a slurry, aging the obtained slurry, separating the solid from the liquid, and then performing a second rinsing to obtain a second solid material;

[0009] (4) Sintering the second solid material to obtain anhydrous iron phosphate.

[0010] Preferably, in step (1), the ratio of the lithium extraction slag to the sulfuric acid solution is 800 g:1200-2000 mL, the concentration of the sulfuric acid solution is 25%-45%; the temperature of the acid dissolution is 30-60° C., and the time is 30-60 min.

[0011] Preferably, in step (1), the molar ratio of iron to phosphorus in the iron-phosphorus mixed solution is (0.94-0.99):1;

[0012] Preferably, in step (2), the volume ratio of the iron-phosphorus mixed solution to the ammonia water is 3 to 4:1; and the mass concentration of the ammonia water is 15% to 25%.

[0013] Preferably, in step (2), the temperature of the precipitation reaction is 50-80° C., the endpoint pH of the precipitation reaction is 1.4-1.9; and the first rinsing is performed until the conductivity is ≤4 ms / cm.

[0014] Preferably, in step (3), the molar ratio of sulfur in the sulfuric acid solution to iron in the iron-phosphorus mixed solution is 0.15:1 to 0.50:1; the slurrying temperature is 20 to 40° C., and the slurrying time is 30 to 60 min.

[0015] Preferably, in step (3), the aging temperature is 70-95° C. and the time is 180-240 min; and the second rinsing is performed until the conductivity is ≤500 μs / cm.

[0016] Preferably, in step (4), the sintering temperature is 500-700° C. and the sintering time is 120-180 min.

[0017] The present invention provides high-tapped iron phosphate prepared by the method described in the above technical solution.

[0018] The present invention provides the application of the high-tap iron phosphate described in the above technical solution in a lithium battery.

[0019] The present invention provides a method for preparing high-tap iron phosphate from lithium-extracted slag, wherein the lithium-extracted slag is mixed with a sulfuric acid solution for acid dissolution to obtain an iron-phosphorus mixed solution; the iron-phosphorus mixed solution and ammonia water are reacted by diagonal addition, rinsed, and an iron-phosphorus filter cake is obtained; the sulfuric acid solution is added for slurrying and aging to obtain wet dihydrate iron phosphate, and anhydrous iron phosphate is obtained after sintering. The present invention optimizes the seeding reaction of iron phosphate to diagonal addition of the iron-phosphorus mixed solution and ammonia water, which can avoid local overacidity or overalkalinity of the slurry during the stirring reaction, and the iron ions and phosphate ions are orderly nucleated during the precipitation reaction, so that the particle size distribution of the iron phosphate is more normally distributed; the type and amount of acid added in the crystallization reaction of the iron phosphate are optimized, sulfuric acid is more acidic than phosphoric acid, and the iron phosphate particles are first dissolved and then crystallized in the crystallization process, so that the primary particles of the iron phosphate are further refined, and the particles are closely agglomerated, and iron phosphate particles with high tap density are successfully prepared. The ferric phosphate prepared by controlling the above process conditions has a small primary particle size, a dense agglomeration of secondary particles, and an extremely high tap density (>1.03 g / cm 3 ).

[0020] The method of the invention has simple process. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The present invention is a process flow chart for preparing high-tapped ferric phosphate;

[0022] Figure 2 The XRD spectrum of anhydrous ferric phosphate prepared in Example 1 of the present invention;

[0023] Figure 3 This is a scanning electron microscope image of anhydrous ferric phosphate prepared in Example 1 of the present invention;

[0024] Figure 4 This is a particle size distribution diagram of anhydrous ferric phosphate prepared in Example 1 of the present invention;

[0025] Figure 5 The XRD spectrum of anhydrous ferric phosphate prepared in Comparative Example 1 of the present invention;

[0026] Figure 6 This is a scanning electron microscope image of anhydrous ferric phosphate prepared in Comparative Example 1 of the present invention;

[0027] Figure 7 This is a particle size distribution diagram of the anhydrous ferric phosphate prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0028] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0029] like Figure 1As shown, the present invention provides a method for preparing high-compacted iron phosphate from lithium-extracting slag, comprising the following steps:

[0030] (1) mixing the lithium extraction slag and sulfuric acid solution, and performing acid dissolution to obtain an iron-phosphorus mixed solution;

[0031] (2) placing the iron-phosphorus mixed solution and ammonia water at two diagonal ends of a reactor, continuously adding the iron-phosphorus mixed solution and ammonia water simultaneously, performing a precipitation reaction, and after solid-liquid separation, performing a first rinsing to obtain a first solid material;

[0032] (3) mixing the first solid material with a sulfuric acid solution to form a slurry, aging the obtained slurry, separating the solid from the liquid, and then performing a second rinsing to obtain a second solid material;

[0033] (4) Sintering the second solid material to obtain anhydrous iron phosphate.

[0034] The invention mixes lithium extraction slag and sulfuric acid solution, performs acid dissolution, and obtains an iron-phosphorus mixed solution.

[0035] The lithium extraction slag of the present invention is preferably the lithium extraction slag obtained after lithium extraction from waste lithium iron phosphate battery pole piece powder. The present invention has no special limitation on the source of the waste lithium iron phosphate battery pole piece and the lithium extraction process. It can be obtained in a manner well known in the art and lithium extracted according to conventional processes.

[0036] In the present invention, in step (1), the amount ratio of the lithium extraction slag and the sulfuric acid solution is preferably 800g:1200-2000mL, more preferably 800g:1500-1800mL, the concentration of the sulfuric acid solution is preferably 25%-45%, more preferably 30%; the temperature of the acid dissolution is preferably 30-60°C, more preferably 40-50°C, and the time is preferably 30-60min, more preferably 40-50min.

[0037] After the acid dissolution is completed, the present invention preferably separates the obtained product into solid and liquid to obtain carbon slag and iron-phosphorus mixed liquid. The present invention has no special limitation on the solid-liquid separation, and it can be carried out in a manner well known in the art.

[0038] In step (1) of the present invention, the molar ratio of iron to phosphorus in the iron-phosphorus mixed solution is preferably (0.94-0.99):1, more preferably 0.95-0.98:1, and further preferably 0.96-0.97:1;

[0039] After obtaining the iron-phosphorus mixed solution, the present invention places the iron-phosphorus mixed solution and ammonia water at two diagonal ends of a reactor, continuously and simultaneously adds the iron-phosphorus mixed solution and ammonia water to perform a precipitation reaction, and after solid-liquid separation, performs a first rinsing to obtain a first solid material.

[0040] In the present invention, in step (2), the volume ratio of the iron-phosphorus mixed solution to aqueous ammonia is preferably 3-4:1, more preferably 3-3.5:1; the mass concentration of the aqueous ammonia is preferably 15%-25%, more preferably 16%.

[0041] In the present invention, in step (2), the temperature of the precipitation reaction is preferably 50-80°C, more preferably 70°C, and the endpoint pH of the precipitation reaction is 1.4-1.9, more preferably 1.5-1.8, and further preferably 1.6-1.65; the precipitation reaction is preferably carried out under stirring conditions; the present invention has no special limitation on the stirring rate, and stirring can be carried out according to conditions well known in the art.

[0042] During the precipitation reaction, Fe in the iron-phosphorus mixed solution 3+ With PO4 3- The combination produces FePO4 precipitation.

[0043] After the precipitation reaction is completed, the present invention separates the solid and liquid of the obtained slurry and then performs a first rinsing to obtain a first solid material.

[0044] After solid-liquid separation, a first mother liquor and a filter cake are obtained, and the obtained filter cake is subjected to a first rinse to obtain a first solid material. The first mother liquor (synthetic mother liquor) obtained in the preparation process of the present invention comprises H + NH 4+ 、SO4 2- , Fe 3+ PO4 3- , and the waste can be disposed of in a manner well known in the art.

[0045] In the present invention, the first rinsing is preferably performed until the conductivity is ≤4 ms / cm, more preferably ≤2.5-3 ms / cm.

[0046] After obtaining the first solid material, the present invention mixes the first solid material with a sulfuric acid solution to perform slurrying, ages the obtained slurry, separates the solid from the liquid, and then performs a second rinsing to obtain the second solid material.

[0047] In the present invention, in step (3), the molar ratio of sulfur in the sulfuric acid solution to iron in the iron-phosphorus mixed solution is preferably 0.15:1 to 0.50:1, more preferably 0.2 to 0.45:1, and further preferably 0.3 to 0.4:1; the mass concentration of the sulfuric acid solution is preferably 3%. In the aging step, the present invention uses sulfuric acid solution as an aging promoter to assist the aging transformation of dihydrate iron phosphate.

[0048] In the present invention, in step (3), the slurrying temperature is preferably 20-40°C, more preferably 25-30°C, and the time is preferably 30-60 min, more preferably 30-40 min; the aging temperature is preferably 70-95°C, more preferably 75-85°C; the time is preferably 180-240 min, more preferably 210-220 min;

[0049] After aging, the solid and liquid are separated to obtain a second mother liquor and a filter cake, and the filter cake is rinsed for a second time to obtain a second solid material, namely, ferric phosphate dihydrate. The second mother liquor (aged mother liquor) obtained in the preparation process of the present invention comprises H + 、SO4 2- , Fe 3+ PO4 3- , and the waste can be disposed of in a manner well known in the art.

[0050] The present invention has no particular limitation on the solid-liquid separation described above, and it can be carried out in a manner well known in the art; in the embodiment of the present invention, it is specifically carried out by filtration.

[0051] In the present invention, the second rinsing is preferably performed until the conductivity is ≤500 μs / cm, more preferably ≤250-400 μs / cm.

[0052] In the present invention, the washing agents used in the first rinsing and the second rinsing are independently preferably pure water.

[0053] After obtaining the second solid material, the present invention sintered the second solid material to obtain anhydrous ferric phosphate.

[0054] In the present invention, the second solid material is preferably dried, sintered, and then ground to obtain anhydrous ferric phosphate; the present invention has no special limitation on the drying and grinding, and the drying and grinding can be carried out according to processes well known in the art.

[0055] In the present invention, in step (4), the sintering temperature is preferably 500-700°C, more preferably 610-650°C; the time is preferably 120-180 min, more preferably 120-150 min. During the sintering process, the ferric phosphate dihydrate first removes crystal water, and then is calcined at high temperature to transform the crystal form to obtain ferric phosphate.

[0056] The present invention provides high-tapped iron phosphate prepared by the method described in the above technical solution.

[0057] The present invention provides the application of the high-tap iron phosphate described in the above technical solution in a lithium battery.

[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] Example 1

[0060] The method for preparing high-compacted iron phosphate from lithium-extracting slag of this embodiment comprises the following steps:

[0061] (1) adding the lithium extraction slag produced by preferential lithium extraction of waste lithium iron phosphate battery pole piece powder to a 30% sulfuric acid solution with a solid-liquid ratio of 800 g:1200 mL, dissolving the solution in acid at a temperature of 40° C. for 30 min, and filtering the solution to obtain an iron-phosphorus mixed solution and carbon slag;

[0062] (2) ensuring that the molar ratio of iron to phosphorus in the iron-phosphorus mixture is 0.96:1, and the required ammonia water is 16% by mass: the iron-phosphorus mixture and the ammonia water are placed at the diagonal ends of the reactor and added, and the two streams of liquid are continuously added for reaction, the volume ratio of the iron-phosphorus mixture and the ammonia water is 4:1, the temperature of the reaction slurry is controlled to be 70° C., the endpoint pH is controlled to be 1.5, the solution is kept in a stirring state during the reaction, the obtained slurry is filtered, and the obtained filter cake is rinsed with pure water until the conductivity is less than 2.5 mS / cm, to obtain a first solid material;

[0063] (3) ensuring that the molar ratio of sulfur in the sulfuric acid solution to iron in the iron-phosphorus mixture is 0.2:1, adding the first solid material to the sulfuric acid solution (mass concentration is 3%) for stirring and slurrying at a temperature of 25° C. for 30 min to obtain a slurry;

[0064] (4) aging the obtained slurry, the aging temperature is controlled at 85° C., the aging time is 180 min, the obtained product is filtered, and the obtained filter cake is rinsed with pure water until the conductivity is below 400 μS / cm, to obtain a second solid material;

[0065] (5) The second solid material is crushed and dried at a temperature of 85° C. After drying, the solid material is sintered at a temperature of 610° C. for 120 min. After sintering, the material temperature is lowered to 50° C. and ground to obtain anhydrous ferric phosphate.

[0066] Example 2

[0067] The method for preparing high-compacted iron phosphate from lithium-extracting slag of this embodiment comprises the following steps:

[0068] (1) adding the lithium extraction slag produced by preferential lithium extraction of waste lithium iron phosphate battery pole piece powder to a 30% sulfuric acid solution with a solid-liquid ratio of 800 g:1500 mL, dissolving the solution in acid at a temperature of 30° C. for 40 min, and filtering the solution to obtain an iron-phosphorus mixed solution and carbon slag;

[0069] (2) ensuring that the molar ratio of iron to phosphorus in the iron-phosphorus mixture is 0.97:1, and the required ammonia water is 16% by mass: the iron-phosphorus mixture and the ammonia water are placed at the diagonal ends of the reactor and added, and the two streams of liquid are continuously added for reaction, the volume ratio of the iron-phosphorus mixture and the ammonia water used is 3.5:1, the reaction slurry temperature is controlled to be 70° C., the endpoint pH is controlled to be 1.65, the solution is kept in a stirring state during the reaction, the obtained slurry is filtered, and the obtained filter cake is rinsed with pure water until the conductivity is less than 2.5 mS / cm, to obtain a first solid material;

[0070] (3) ensuring that the molar ratio of sulfur in the sulfuric acid solution to iron in the iron-phosphorus mixture is 0.3:1, adding the first solid material to the sulfuric acid solution (mass concentration is 3%) for stirring and slurrying at a slurrying temperature of 30° C. for 40 min to obtain a slurry;

[0071] (4) aging the obtained slurry, the aging temperature is controlled at 85° C., the aging time is 210 min, the obtained product is filtered, and the obtained filter cake is rinsed with pure water until the conductivity is below 400 μS / cm, to obtain a second solid material;

[0072] (5) The second solid material is crushed and dried at a temperature of 85° C. After drying, the solid material is sintered at a temperature of 610° C. for 150 min. After sintering, the material temperature is lowered to 50° C. and ground to obtain anhydrous ferric phosphate.

[0073] Example 3

[0074] The method for preparing high-compacted iron phosphate from lithium-extracting slag of this embodiment comprises the following steps:

[0075] (1) adding the lithium extraction slag produced by preferential lithium extraction of waste lithium iron phosphate battery pole piece powder to a 30% sulfuric acid solution with a solid-liquid ratio of 800 g:1800 mL, dissolving the solution in acid at a temperature of 50° C. for 50 min, and filtering the solution to obtain an iron-phosphorus mixed solution and carbon slag;

[0076] (2) ensuring that the molar ratio of iron to phosphorus in the iron-phosphorus mixture is 0.98:1, and the required ammonia water is 16% by mass: the iron-phosphorus mixture and the ammonia water are placed at the diagonal ends of the reactor and added, and the two streams of liquid are continuously added for reaction, the volume ratio of the iron-phosphorus mixture and the ammonia water is 3:1, the temperature of the reaction slurry is controlled to be 70° C., the endpoint pH is controlled to be 1.8, the solution is kept in a stirring state during the reaction, the obtained slurry is filtered, and the obtained filter cake is rinsed with pure water until the conductivity is less than 2.5 mS / cm, to obtain a first solid material;

[0077] (3) ensuring that the molar ratio of sulfur in the sulfuric acid solution to iron in the iron-phosphorus mixture is 0.4:1, adding the first solid material to the sulfuric acid solution (mass concentration is 3%) for stirring and slurrying at a slurrying temperature of 35° C. for 60 min to obtain a slurry;

[0078] (4) aging the obtained slurry at a temperature of 85° C. for 240 min, filtering the obtained product, and rinsing the obtained filter cake with pure water until the conductivity is below 400 μS / cm, thereby obtaining a second solid material;

[0079] (5) The second solid material is crushed and dried at a temperature of 85° C. After drying, the solid material is sintered at a temperature of 610° C. for 180 min. After sintering, the material temperature is lowered to 50° C. and ground to obtain anhydrous ferric phosphate.

[0080] Comparative Example 1

[0081] The method for preparing iron phosphate from lithium slag in this comparative example comprises the following steps:

[0082] (1) adding the lithium extraction slag produced by preferential lithium extraction of waste lithium iron phosphate battery pole piece powder to a 30% by mass sulfuric acid solution with a solid-liquid ratio of 800 g:1200 mL, dissolving the solution in acid at a temperature of 40° C. for 30 min, and filtering the solution to obtain an iron-phosphorus mixed solution and carbon slag;

[0083] (2) ensuring that the molar ratio of iron to phosphorus in the iron-phosphorus mixture is 0.96:1, and the required ammonia water is 16% by mass: the iron-phosphorus mixture and the ammonia water are placed on the same side of the reactor, and two streams of feed liquid are continuously added for reaction, the volume ratio of the iron-phosphorus mixture to the ammonia water is 4:1, the reaction slurry temperature is controlled to be 70° C., the endpoint pH is controlled to be 1.5, and the solution is kept in a stirring state during the reaction to obtain slurry 1;

[0084] (3) Slurry 1 was subjected to solid-liquid separation and rinsed with pure water until the conductivity was below 2.5 mS / cm to obtain filter cake E1;

[0085] (4) ensuring that the molar ratio of phosphorus in the phosphoric acid dilute solution to iron in the iron-phosphorus mixed solution is 0.2:1, adding the filter cake to the phosphoric acid dilute solution (mass concentration is 3%) and stirring to obtain slurry 2;

[0086] The slurry 2 was aged at a temperature of 85° C. for 180 min to obtain slurry 3; the slurry 3 was solid-liquid separated and rinsed with pure water until the conductivity was below 400 μS / cm to obtain filter cake E2;

[0087] (5) The filter cake E2 is crushed and dried at a temperature of 85°C. After drying, it is sintered at a temperature of 610°C for 120 min. After sintering, the material temperature is lowered to 50°C and anhydrous iron phosphate is obtained by grinding.

[0088] Characterization and testing

[0089] Figure 2 The XRD spectrum of anhydrous ferric phosphate prepared in Example 1 of the present invention; Figure 2 It can be seen that the XRD diffraction peak of the prepared iron phosphate material has no obvious peak separation phenomenon, so the iron phosphate prepared by the present invention has a high purity.

[0090] Figure 3 This is a scanning electron microscope image of anhydrous ferric phosphate prepared in Example 1 of the present invention; Figure 4 This is a particle size distribution diagram of anhydrous ferric phosphate prepared in Example 1 of the present invention;

[0091] Figure 5 The XRD spectrum of anhydrous ferric phosphate prepared in Comparative Example 1 of the present invention is shown in FIG. Figure 5 It can be seen that the XRD diffraction peaks of the prepared iron phosphate have no obvious peak separation phenomenon.

[0092] Figure 6 This is a scanning electron microscope image of anhydrous ferric phosphate prepared in Comparative Example 1 of the present invention; Figure 7 This is a particle size distribution diagram of anhydrous ferric phosphate prepared in Comparative Example 1 of the present invention;

[0093] Figure 3 and Figure 6 Comparison of the scanning electron microscope images of the iron phosphate prepared in Example 1 and Comparative Example 1 shows that the primary particles of the iron phosphate prepared in Example 1 are smaller and the secondary particles are more densely agglomerated.

[0094] Figure 4 and Figure 7 By comparison, it can be seen that the particle size distribution of the iron phosphate prepared in Example 1 is closer to the normal distribution.

[0095] The ferric phosphate prepared in Examples 1 to 3 and Comparative Example 1 was tested using a Malvern 2000 particle size analyzer. The results are shown in Table 1.

[0096] Table 1 Comparison of particle size distribution of iron phosphate prepared in Examples 1 to 3 and Comparative Example 1

[0097] sample Example 1 Example 2 Example 3 Comparative Example 1 D10(μm) 0.98 0.86 0.76 1.45 D50(μm) 2.75 2.43 2.66 7.75 D90(μm) 8.63 10.61 9.35 19.39

[0098] It can be seen from Table 1 that the particle size D10 of the iron phosphate prepared in Examples 1 to 3 of the present invention is less than 1.0 μm, and is smaller than the particle size D10 of the iron phosphate prepared in Comparative Example 1. This is because sulfuric acid aging during the crystallization reaction makes the primary particles of the iron phosphate finer.

[0099] The iron phosphate prepared in Examples 1 to 3 and Comparative Example 1 was tested using a tap density meter. The results are shown in Table 2.

[0100] Table 2 Comparison of tap density of iron phosphate prepared in Examples 1 to 3 and Comparative Example 1

[0101] sample Example 1 Example 2 Example 3 Comparative Example 1 <![CDATA[Tap density (g / cm 3 )]]> 1.037 1.054 1.041 0.753

[0102] As shown in Table 2, the tap density of the iron phosphate prepared in Examples 1 to 3 of the present invention all reached 1.03 g / cm 3 The above is due to the fact that the aging of sulfuric acid during the crystallization reaction makes the primary particles of iron phosphate smaller. At the same time, the simultaneous addition of feed liquid during the seed reaction makes the secondary particles of iron phosphate more compact, minimizing the stacking gaps between particles to the greatest extent, thereby significantly improving the tap density of iron phosphate.

[0103] The tap density of the iron phosphate product obtained in Comparative Example 1 is only 0.753 g / cm 3 This is because the primary particles of iron phosphate prepared in this comparative example are coarser, so that there are more gaps inside the secondary particles formed, and there are larger gaps between the particles.

[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing high-compacted iron phosphate from lithium-extracting slag, characterized in that: The following steps are involved: (1) mixing the lithium extraction slag and sulfuric acid solution, and performing acid dissolution to obtain an iron-phosphorus mixed solution; (2) placing the iron-phosphorus mixed solution and ammonia water at two diagonal ends of a reactor, continuously adding the iron-phosphorus mixed solution and ammonia water simultaneously, performing a precipitation reaction, and after solid-liquid separation, performing a first rinsing to obtain a first solid material; (3) mixing the first solid material with a sulfuric acid solution to form a slurry, aging the obtained slurry, separating the solid from the liquid, and then performing a second rinsing to obtain a second solid material; (4) Sintering the second solid material to obtain anhydrous iron phosphate.

2. The preparation method according to claim 1, characterized in that: In step (1), the amount ratio of the lithium extraction slag to the sulfuric acid solution is 800g:1200-2000mL, the concentration of the sulfuric acid solution is 25%-45%; the temperature of the acid dissolution is 30-60°C, and the time is 30-60min.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), the molar ratio of iron element to phosphorus element in the iron-phosphorus mixed solution is (0.94-0.99):

1.

4. The preparation method according to claim 1, characterized in that: In step (2), the volume ratio of the iron-phosphorus mixed solution to the ammonia water is 3-4:1; and the mass concentration of the ammonia water is 15%-25%.

5. The preparation method according to claim 1 or 4, characterized in that: In step (2), the temperature of the precipitation reaction is 50-80° C., and the endpoint pH of the precipitation reaction is 1.4-1.9; the first rinsing is performed until the conductivity is ≤4 ms / cm.

6. The preparation method according to claim 1, characterized in that: In step (3), the molar ratio of sulfur in the sulfuric acid solution to iron in the iron-phosphorus mixed solution is 0.15:1 to 0.50:1; the slurrying temperature is 20 to 40° C., and the slurrying time is 30 to 60 minutes.

7. The preparation method according to claim 1 or 6, characterized in that: In step (3), the aging temperature is 70-95° C. and the time is 180-240 min; and the second rinsing is performed until the conductivity is ≤500 μs / cm.

8. The preparation method according to claim 1, characterized in that: In step (4), the sintering temperature is 500-700° C. and the sintering time is 120-180 min.

9. High-tapped iron phosphate prepared by the method according to any one of claims 1 to 8.

10. Use of the high-tap iron phosphate according to claim 9 in lithium batteries.

Citation Information

Patent Citations

  • Synthesis process of battery-grade iron phosphate

    CN110540185A

  • Method for recovering iron phosphate from iron-phosphorus slag after lithium extraction of lithium iron phosphate battery

    CN111646447A